Banco de Leite Humano : uma análise das diferenças entre as doadoras adultas e adolescentes no ano de 2004 - Genovez, Christyna Beatriz (2005)
Nowadays, the problem of pregnancy in adolescence has assumed significant proportions and, in this study, the adolescent group is quite expressive, and the Human Milk Donors (HM) present age, cultural and socioeconomic differences among each others, demanding from the professionals of health abilities to know how to work with these peculiar conditions. In this sense, this study aimed at analyzing the population's profile to point out differences among adult and adolescent donors, to verify the type of the most frequent collection and if the donation of HM corresponds to the preconizations of the Regulation 322/88. It was a traverse, analytic study carried out in the Human Milk Bank (HMB) of Maringá-PR. The population of the study was the total of registered donors in the year 2004 (443) and the source of data was the Record of Donors' Registration. Socioeconomic, demographic, perinatal variables related to the human milk donation were analyzed. The age variable was divided in adolescent donors (< 20 years old) and adult donors (>=20 years old) and according to that, the condition of being adolescent donor was considered as dependent variable, being interactions and differences between the latter and the other variables of the study tested. Frequency of 16.35% of adolescents was observed. Significant statistical association (p < 0.001) among adolescent women and low family income, living without companion, prematurity and cesarean childbirth were found. Results show that the adolescent donors need differentiated service and greater incentive for the breastfeeding practice, for they present socioeconomic and unfavorable perinatal conditions.